Marie Curie Initial Training Networks - (:unkn) unknown (My University, 2026)
Training & Research in Polymer Optical fibre grating sensor Devices “TRIPOD”, PEOPLE MARIE CURIE ACTIONS, Marie Curie Initial Training Networks, FP7-PEOPLE-2013-ITN, European Union, 300K